An evaluation of the breast and cervical cancer prevention program in Paranapanema, Sao Paulo, Brazil - Canido, Rolando Enrique; Mota de Carvalho, Geraldo; Barbosa Merighi, Miriam Aparecida; Martins, Alder Antônio (O Mundo da Saúde, 2007)
Gynecological cancers are responsible for a dramatic morbidity and mortality rate among women, constituting a public health problem in the country. The goal of this study was to evaluate the results obtained in the Breast and Cervical Cancer Prevention Program in Paranapanema, Sao Paulo, suggesting the implantation of routines, conducts, and regulations to make this assistance faster, making easier collecting material for tests and procedures for solving alterations presented. The city got beyond the target set by the Health Regional Board in the campaign for gynecological cancer prevention promoted by the Health Ministry, from March to May, 2002. The staff showed to be well-trained for the Gynecological Cancer Prevention Program. Physical resources were sufficient and the process complied with the recommendation from the Health Ministry, but there is still a need of a few minor adaptations. The lack of a protocol makes difficult providing assistance and tracking changes and this may cause a late diagnosis of cancer.